Development of sodium chlorite and glucono delta-lactone incorporated PLA film for microbial inactivation on fresh tomato. (June 2020) - Zhou, Siyuan; Jin, Tony; Sheen, Shiowshuh; Zhao, Guohua; Liu, LinShu; Juneja, Vijay; Yam, Kit
Graphical abstract: Highlights: PLA film with control release of ClO2(g) was developed. Different formula and storage conditions showed varying ClO2(g) release rates. ClO2(g) release properties were well maintained after 4 weeks of ambient storage. PLA film efficiently inactivated both Salmonella and E. coli O157:H7. Sensory properties of treated tomato were not affected after 14-days of storage. Abstract: Chlorine dioxide (ClO2 ) is an effective disinfectant used in the sanitization of fresh produce. Glucono delta-lactone (GDL), widely used as an acidifier during food processing, can be partially hydrolyzed to become a weak acid—gluconic acid under chemical equilibrium upon dissolution in water. This study focused on the development of a novel polylactic acid (PLA) film which incorporated with sodium chlorite (NaClO2 ) and GDL for ClO2(g) generation. The effects of PLA amount, NaClO2  + GDL/PLA ratio, NaClO2 /GDL ratio, temperature and relative humidity on the release profiles of ClO2(g) were elucidated. The storage test indicated that film efficacy was well maintained after 4 weeks of storage under ambient conditions. The microbial inactivation results revealed that ClO2(g) generated from the films reduced populations of surface-inoculated Salmonella and Escherichia coli O157:H7 from ca. 5 log CFU/tomato to undetectable level (<1 log CFU/tomato) within 2 and 4 h respectively and the complete elimination in populations of both bacterial species was maintained throughout the 14-day storage period at both 10 and 22 °C. The sensory properties of treated tomatoes were evaluated and exhibited no significant difference (p > 0.05) compared to controls except for appearance on day 14 under 22 °C storage.